Satisfaction indicators and occupation habits of spanish elders in their housing during the Covid-19 confinement - Cuerdo Vilches, Teresa; Navas Martín, Miguel Ángel (WPS Review International on Sustainable Housing and Urban Renewal, 2020)
The coronavirus pandemic has led countries to confine the population to minimize the impact of COVID-19. This measure has meant that households permanently and continuously shared the domestic space, during the validity period of the public health measure. The way of living the experience has been very different according to the socioeconomic characteristics of the population, as well as the composition of the household, affecting the way of adapting their habits, routines and occupations. For older people, particular circumstances, such as the greater tendency to live in solitude, or the work situation, has conditioned the way of experiencing this situation. The findings show a certain status and stability, which affects different areas of life. This was reflected in the qualities and satisfaction with the home, in certain maintenance of habits and routines, and in general caution when going outside.